The Implementation of Teaching Speaking Using Differentiated Learning - Thohari, Khamim; Kurniawan, Erwin Hari; Sulistyanto, Irwan (Prosiding Seminar, 2023)
Differentiated learning is creating a diverse class by providing opportunities to acquire content, process an idea and improve each student's results so students can learn more effectively. The purpose of this article is to explain the concept of differentiated learning. This qualitative research took the background of class 7th 0f SMP Ar-Risalah Lirboyo. Observation, interviews, and documentation were employed in the collection of data. Data analysis was performed by qualitative data analysis. The study's findings indicate that there are differentiated learning objectives that include: coordinating learning by paying attention to learning interests, learning readiness, and learning preferences; assisting all in learning so that all students can achieve learning objectives; increasing motivation and student learning outcomes; establishing harmonious relationships between teachers and students so that students are more enthusiastic about learning; and assisting students in achieving their learning objectives. Differentiated learning allows students to learn organically and efficiently with teachers who can collaborate on the necessary methods and